Importance of Leaf Epidermal Characters in the Asteraceae Family - Adedeji, O.; Jewoola, O. A. (2014)
A comparative study of the leaf epidermis of twelve species in the Compositae (Asteraceae) family was undertaken in order to document characters that are important in the taxonomy of the family. It was observed that trichomes can be successfully used for the delimitation of genera within the family. Within each species however, there are varied assortment of trichomes with occasional transitions among them. Launaea taraxacifolia was unique in being the only species without any trichomes. Stellate trichome type and K-shaped or tetraradiate trichomes were observed in Tridax procumbens only. The genus Vernonia can be delimited from the other genera by the possession of T - shaped trichomes which are absent in the other genera, while amoeboid-shaped trichomes can be found in the genus Chromolaena only. Within the same genus, the species can also be delimited on the basis of possession of unique trichome types, for example in the genera Vernonia and Emilia. Cuticular striations occur in only two species out of the twelve studied, on the abaxial surface of V. amygdalina and on both surfaces of Bidens pilosa. Four stomatal types were recorded for the family, anomocytic, brachyparacytic, anisocytic and diacytic. Stomatal type was observed to delimit not only at generic level, but also at specific or species level. Ageratum conyzoides and Syndrella nodiflora are the only two species with occasional diacytic stomatal types. Results of the statistical correlation analysis for stomatal size and stomatal index at the 0.05 and 0.01 levels revealed high positive correlation for species in the same tribe, as well as for species in different tribes affirming close interrelationship and overlap of the values of stomatal indices and sizes within the family. Foliar anatomical characters that justify the separation of Vernonia amygdalina and Vernonia cinerea into separate tribes are highlighted.